2002
DOI: 10.1161/01.str.0000028235.91778.95
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Dementia After Ischemic Stroke

Abstract: Background and Purpose-A number of cross-sectional epidemiological studies have reported that one fourth of elderly patients meet criteria for dementia 3 months after ischemic stroke, but few longitudinal studies of the incidence of dementia after stroke have been performed. We conducted the present study to investigate the incidence and clinical predictors of dementia after ischemic stroke. Methods-We administered neurological, neuropsychological, and functional assessments annually to 334 ischemic stroke pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
187
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(203 citation statements)
references
References 51 publications
8
187
2
6
Order By: Relevance
“…41,42,46 Some studies 31 found that stroke patients with high blood pressure correlate of dementia and other studies 26,30 also found that hypertension associated with an increased prevalence of post-stroke dementia. In contrast, other studies 23,28 found that hypertension have not been associated with increased risk of dementia in stroke patients. The result of this study found that stroke patients with hypertension risk of dementia were 1.36 times compared with stroke patients without hypertension statistically significant.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…41,42,46 Some studies 31 found that stroke patients with high blood pressure correlate of dementia and other studies 26,30 also found that hypertension associated with an increased prevalence of post-stroke dementia. In contrast, other studies 23,28 found that hypertension have not been associated with increased risk of dementia in stroke patients. The result of this study found that stroke patients with hypertension risk of dementia were 1.36 times compared with stroke patients without hypertension statistically significant.…”
Section: Discussionmentioning
confidence: 67%
“…Consistent with other studies 26,30,31 that reported association between stroke patients with and without previous transient ischemic attack found that previous transient ischemic attack correlate of dementia. In contrast other studies 21,28 showed that previous transient ischemic attack have not been associated with dementia in stroke patients.…”
Section: Reviewmentioning
confidence: 60%
See 3 more Smart Citations